2015
DOI: 10.1007/s11103-015-0374-2
|View full text |Cite
|
Sign up to set email alerts
|

G-protein α-subunit (GPA1) regulates stress, nitrate and phosphate response, flavonoid biosynthesis, fruit/seed development and substantially shares GCR1 regulation in A. thaliana

Abstract: Heterotrimeric G-proteins are implicated in several plant processes, but the mechanisms of signal-response coupling and the roles of G-protein coupled receptors in general and GCR1 in particular, remain poorly understood. We isolated a knock-out mutant of the Arabidopsis G-protein α subunit (gpa1-5) and analysed its transcriptome to understand the genomewide role of GPA1 and compared it with that of our similar analysis of a GCR1 mutant (Chakraborty et al. 2015, PLoS ONE 10(2):e0117819). We found 394 GPA1-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 70 publications
6
49
0
1
Order By: Relevance
“…For example, overexpression of miRNA444a in rice plants, an Pi-starvation-inducible gene, led to the activation of nitrate signaling pathway only under Pi-starvation conditions, which resulted in transgenic plants to produce longer primary roots with fewer lateral roots compared to wild-type (Yan et al, 2014). Similarly, the transcriptome analysis of gpa1-5 mutant which exhibited several developmental phenotypes including the presence of longer roots with fewer lateral roots also revealed the induction of several nitrate starvation/assimilation genes such as NRT2.1, ICDH , and ASN1 and reduction of phosphate use efficiency genes such as WRKY75, PHT1 , and LPR1 compared to wild-type (Chakraborty et al, 2015). Remarkably, the development of primary root under Pi deficient conditions was found to be largely dependent on the presence of nitrate in the growth medium, which is suppressed by nitrate-inducible HRS1 and HHO1 transcription factors (Medici et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…For example, overexpression of miRNA444a in rice plants, an Pi-starvation-inducible gene, led to the activation of nitrate signaling pathway only under Pi-starvation conditions, which resulted in transgenic plants to produce longer primary roots with fewer lateral roots compared to wild-type (Yan et al, 2014). Similarly, the transcriptome analysis of gpa1-5 mutant which exhibited several developmental phenotypes including the presence of longer roots with fewer lateral roots also revealed the induction of several nitrate starvation/assimilation genes such as NRT2.1, ICDH , and ASN1 and reduction of phosphate use efficiency genes such as WRKY75, PHT1 , and LPR1 compared to wild-type (Chakraborty et al, 2015). Remarkably, the development of primary root under Pi deficient conditions was found to be largely dependent on the presence of nitrate in the growth medium, which is suppressed by nitrate-inducible HRS1 and HHO1 transcription factors (Medici et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…WDD1 encodes a transducin/ WD40 repeat-like protein annotated as a putative b-subunit of a heterotrimeric G-protein complex. Recently, G-protein-mediated signaling was associated with the WRKY75-dependent regulation of PSI genes (Chakraborty et al, 2015). This could explain the high impact of the knockout of WDD1 on yellow and red coexpression modules in P-limited roots, two modules that are largely associated with processes involved directly in Pi signaling and Pi homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The XLGs are involved in growth, development, and defending systems [8][9][10]. The results of transcriptome analysis confirmed that GCR1 affects the response of plants to biotic and abiotic stress, hormones, secondary metabolism, and phosphate starvation [11,12]. However, the accurate roles of GCR1 remain unknown.…”
Section: Introductionmentioning
confidence: 85%